2021
DOI: 10.1002/prp2.725
|View full text |Cite
|
Sign up to set email alerts
|

Intervention by clinical pharmacists can improve blood glucose fluctuation in patients with diabetes and acute myocardial infarction: A propensity score‐matched analysis

Abstract: Acute phase hyperglycemia and exaggerated glucose fluctuation may be associated with poor outcomes in diabetic patients after acute myocardial infarction (AMI). This study aimed to determine whether intervention by clinical pharmacists can mitigate blood glucose and glucose fluctuations in these fragile patients. This retrospective study enrolled patients with diabetes and AMI, from 1 January 2019 to 30 June 2020 in our institution. Blood glucose and glucose fluctuations were calculated before and after the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…A series of methods can effectively reduce glucose fluctuation in diabetic patients. Shi, F. H ( 21 ) found that the clinical pharmacist intervention contributed to improved outcomes, specifically, in reducing blood glucose fluctuations and potential hypoglycemia risk. However, some drugs have advantages in controlling glucose homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…A series of methods can effectively reduce glucose fluctuation in diabetic patients. Shi, F. H ( 21 ) found that the clinical pharmacist intervention contributed to improved outcomes, specifically, in reducing blood glucose fluctuations and potential hypoglycemia risk. However, some drugs have advantages in controlling glucose homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…They will discuss with the patient to evaluate their practice on therapies, glucose monitoring, diet, and exercise. The intervention for each patient will be noted and intimated to the diabetes care team [ 6–8 ].…”
Section: Role Of Clinical Pharmacistmentioning
confidence: 99%
“…Through consultation and protocol development, improved hyperglycemia management by pharmacists is possible. 40,41 Solid organ transplantation (SOT) has seen many successes with the addition of the pharmacist into the care team. Posttransplant, up to 90% of patients can experience transient hyperglycemia that often requires short-term treatment with antihyperglycemic agents, while others may go on to develop post-transplant diabetes.…”
Section: Alternative Care Modelsmentioning
confidence: 99%
“…9,15,18 Studies that looked at the use of telehealth-based visits saw similar improvements in A1c. 49,50 Other diabetes-specific outcomes reported on include time to treatment intensification, 25 time needed to reach A1c goal, 22 number of daily insulin injections, daily units of insulin injected, 11 diabetes-related interventions made per patient per year, 8 reduction in fluctuation of blood glucose, hypoglycemia reduction, 40 appropriate deprescribing, 51 and patient and clinician reported barriers to achieve glycemic control. 18…”
Section: Dovepressmentioning
confidence: 99%